“Informativo matinal para ahorrar tiempo”. An alternative newscast with its own fandom - Cano-Orón, Lorena (2024)
Comedian Ángel Martín edits and presents the Informativo matinal para ahorrar tiempo (IMPAT), a daily two-minute audiovisual newscast distributed on major social networks, with a daily audience of around one million views. This format has generated a community of followers who expand its original content by creating mimetic sector-specific news programs. This study analyzes the thematic agenda and stylistic features of the IMPAT, as well as the news programs developed by its followers. The results show a predominance of soft news and non-news content, as well as the presence of narrative traits characteristic of infotainment. The followers expand the IMPAT by creating their own news programs, also focused on soft news and with similar styles. Thus, IMPAT stands out as an alternative newscast around which a unique informational fandom has been consolidated, with content generated by its users as news prodesigners.